Ibáñez Rodríguez, Miguel (2020). Enotradulengua. Vino, lengua y traducción. Berlín: Peter Lang - Martínez Martínez, Silvia (Sendebar, 2022)
Reseña de Ibáñez Rodríguez, Miguel (2020). Enotradulengua. Vino, lengua y traducción. Berlín: Peter Lang, 368 pp.